From Documentary Realism to Figurative Realism: Igort's The Ukrainian and Russian Notebooks and the Holodomor. Issue 3 (December 2018) - Nayar, Pramod K.
Abstract : This essay examines the five stories on the Holodomor in Igort's graphic memoir, The Ukrainian and Russian Notebook s: Life and Death under Soviet Rule (English translation, 2016). It argues that the trauma-aesthetic in Igort's work demonstrates a shift from the documentary realist mode through a participatory documentary mode to a figurative realism. If the first seeks to deliver the tragedy of the Holodomor through a certain distanced objective perspective, the second smoothly undermines it by showing us the subjective mediation, of survivors and Igort. The third complicates the trauma by turning humans into ghosts in what the essay argues is a new trauma-aesthetic.